2018
DOI: 10.1590/s1980-6574201700si0086
|View full text |Cite
|
Sign up to set email alerts
|

Screen-based sedentary behaviors, mental health, and social relationships among adolescents

Abstract: -Aim:To analyze the association between screen-based sedentary behaviors, mental health, and social relationships in Brazilian adolescents. Methods: A representative sample of the adolescents from Londrina/PR was selected (n = 1,158; 10 to 17 y). Weekday and weekend screen time (TV-viewing and computer/video-game), mental health indicators (self-rated health, stress, feelings of sadness, and satisfaction with own body), and perceived social relationships (friends, family, and teachers) were collected through q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
4
0
1
Order By: Relevance
“…However, most of the studies looking at SB and mental health have focused on children or adolescents [16][17][18]. One study examined SB and stress symptoms among Korean adults and found that prolonged sedentary time was significantly associated with a greater risk of stress symptoms [19].…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%
“…However, most of the studies looking at SB and mental health have focused on children or adolescents [16][17][18]. One study examined SB and stress symptoms among Korean adults and found that prolonged sedentary time was significantly associated with a greater risk of stress symptoms [19].…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%
“…Además, se identificó una asociación significativa entre mayor tiempo de uso de pantallas durante el fin de semana y menor puntaje de calidad de vida en el dominio "relaciones sociales". Si bien esta asociación específica no ha sido ampliamente explorada en la literatura, estudios previos a la pandemia efectuados en adolescentes muestran que un mayor uso de dispositivos durante el fin de semana, tales como computadores o videojuegos, se asocian a una mayor probabilidad de insatisfacción respecto a indicadores de interacción social como relaciones familiares y de amistad (Rodrigues Da Silva et al, 2018).…”
Section: Discussionunclassified
“…However, other studies have shown that social media use can reduce face-to-face interactions between people as well as users’ participation in meaningful social activities and that sedentary behavior leads to increased screen time ( Guernsey, 2014 ). Sedentary behavior caused by social media use greatly increases the risk of physical health problems ( Silva et al, 2017 ). The use of social media may also lead to internet addiction.…”
Section: Related Literaturementioning
confidence: 99%